Role of green areas for space integration of Kraków’s Metropolitan Area - Hrehorowicz-Gaber, Hanna (Bulletin of Geography. Socio-economic Series, 2015)
The Kraków Metropolitan Area (KOM) is a specific functional region comprising a big city that is the Kraków metropolis, together with its neighbouring complex of settlements with a variety of mutual interactions. The social and economic space requires multi-dimensional enhancement of its interrelations and partial rehabilitation of its developed areas; it constitutes, at the same time, a potential which strengthens the position of Kraków as a European city. A clear structure of the metropolitan area and its internal links through green seams provide the basis for functional and spatial integration of the metropolis. The greenery, comprised in larger natural structures such as river parks and green wedges, enhances the area’s polycentric concept. The shaping of the urban tissue of Kraków and its suburban zone by composing and building a network of open spaces is the basic criterion for developing a coherent metropolitan area with a sustainable structure. Many problems of the urban environment and its surroundings can be fully understood through their analyses in various scales. In order to better illustrate this complex system of interrelations, reference should be made in analyses to the macroregional scale then narrowing them to the regional scale, to ultimately go down to the metropolis. The issues covered in the paper concern open areas which should not be discussed without a broader spectrum because the notion of green areas is understood to mean primarily spaces which are networked and intertwined with the settlement structure. Some of them are clear, for instance the greenery which accompanies water courses, and easy to identify. Marshlands are mostly linearly continuous and this makes them coherent in their nature. Other green areas (apart from larger forest complexes) are not of essential significance for the integration of the metropolis. The example of Kraków shows that the KOM (1) has a big potential expressed through its natural environment in the form of green areas. The anthropopressure, however, is so high that open spaces are being absorbed by developments. It is riverside areas which have retained a clear structure of interrelations and they should be perceived as the future for the links in the metropolitan area.